2021
DOI: 10.1021/jacs.0c12512
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Microdroplets Capture Elusive Carbocations

Abstract: Carbocations are short-lived reactive intermediates in many organic and biological reactions that are difficult to observe. This field sprung to life with the discovery by Olah that a superacidic solution allowed the successful capture and nuclear magnetic resonance characterization of transient carbocations. We report here that water microdroplets can directly capture the fleeting carbocation from a reaction aliquot followed by its desorption to the gas phase for mass spectrometric detection. This was accompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 42 publications
(69 reference statements)
4
47
1
Order By: Relevance
“…Spectroscopic information coupled with MS measurements would be very valuable to identify the electronic and geometric structures of chemical intermediates in solution. Ambient ionization techniques such as ESI and desorption ESI (DESI) have been extensively used for chemical reactions characteristic of charged droplets or as probes for chemical reactions in bulk phases. ,,, Hence, the application of new spectroscopic techniques to MS measurements will open a new area of growing interest for reaction chemistry and photochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopic information coupled with MS measurements would be very valuable to identify the electronic and geometric structures of chemical intermediates in solution. Ambient ionization techniques such as ESI and desorption ESI (DESI) have been extensively used for chemical reactions characteristic of charged droplets or as probes for chemical reactions in bulk phases. ,,, Hence, the application of new spectroscopic techniques to MS measurements will open a new area of growing interest for reaction chemistry and photochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical intermediates are generally not very abundant in solution because of their short lifetimes, which prevents their selective detection. In the last three decades, extensive efforts have been devoted to detecting chemical intermediates in solution using mass spectrometric (MS) techniques. MS studies determined the molecular weight or atomic constituents of the species, but predictions by quantum chemical calculations or chemical intuition were needed to estimate the electronic and geometric structures of the intermediates. Roithová et al reported pioneering studies of photochemical intermediates in the gas phase using ion spectroscopy to examine the reaction mechanism in solution. , They used ion-mobility mass spectrometry, infrared photodissociation spectroscopy, and visible photodissociation spectroscopy to identify photochemical intermediates produced in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical intermediates are generally not very abundant in solution due to their short lifetimes, which prevents their selective detection in the solution. In the last three decades, several mass spectrometric (MS) techniques have been extensively applied to the chemical intermediates produced in solutions. These studies could determine the molecular weight or the atomic constituents of the species; however, spectroscopic investigations are required to predict the structure of the intermediates. Recently, Mayer and Asmis reported the gas-phase IR spectroscopy of chemical intermediates produced using a microfluidic chip-reactor …”
Section: Introductionmentioning
confidence: 99%
“…The droplet evolution on a millisecond time scale desorbs reactive (metal-free) carbanions to the gas phase for mass spectrometric detection, allowing real-time monitoring of the formation of such reactive species as intermediates. This work is influenced by our recent study that electrohydrodynamically generated water microdroplets can intercept, stabilize, and transfer very effectively reactive carbocations from a reaction medium to the gas phase for mass spectrometric detection. , However, this report presents a strikingly different result: unlike carbocations, carbanions better survive in aqueous microdroplets containing methanol or acetonitrile. In addition to the carbanion stability in microdroplets, we also investigated the possible factors that may cause this difference.…”
mentioning
confidence: 98%